Experimental Analysis of the Changes in Coral Sand Beach Profiles under Regular Wave Conditions - Zhen Yao; Jie Chen; Changbo Jiang; Hai Liang; Zhiyuan Wu; Bin Deng; Yuannan Long; Chen Bian (Journal of Marine Science and Engineering, 2024)
This study utilized 50 laboratory experiments to document the evolution of coral beaches under varying regular wave conditions, including five distinct wave periods and ten wave heights. Both the type of equilibrium beach and the shape of sand bars were used to represent beach evolution. The evolution of coral sand beaches was then compared to quartz sand beaches. The experimental results show that the predicted (modeled) equilibrium profile of a quartz sand beach was not applicable to coral sand beaches. Compared to sand bars on quartz sand beaches, the distance from bar crests to the beach berm in coral sand beaches was greater, whereas the erosional depth of sand troughs was deeper. However, the grain size distribution of sand associated with the coral sand beach under wave action was consistent with Celikoglu’s law. Both an equilibrium beach profile classification model and a sand bar shape prediction model for coral sand beaches were developed based on the experimental data.